Physical Distancing Visual Communication for Congregational Prayers as an Implementation of Health Protocols - Widyoputro, Muhammad Kholif Lir (Journal of Architectural Research and Design Studies, 2022)
Mosques are a place for physical activity that has great potential to become a cluster for the spread of the COVID-19 virus. At the beginning of the pandemic, mosques were prohibited from operating to carry out various Islamic religious activities, especially congregational prayers. Mosque administrators play a role in communicating the importance of maintaining a safe distance between prayers to contain the spread of the virus. Visual communication with distance markers between worshipers is an efficient way of implementing social distancing in the prayer room. The method used in this research is descriptive qualitative for secondary data. The approach used is desk research. This research finds that there is no standard signage for physical distancing as an implementation of health protocol in the mosque. This is indicated by various signage configurations and approaches. There is a need for congregation prayer physical distancing visual signage standardization on a regional or national scale. Keywords: architectural visual communication, Covid-19, physical distancing, proximity